AN ANALYSIS OF MEDICAL TOURISM AND ITS ROLE IN INDIA’S ECONOMIC DEVELOPMENT - Soni, Dinesh C. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India has emerged as a prominent global hub for medical tourism, owing to its cost-effective healthcare services, highly qualified medical professionals, and the integration of traditional treatment systems such as AYUSH (Ayurveda, Yoga & Naturopathy, Unani, Siddha, and Homeopathy).. The economic impact of medical tourism in India over the last five years is examined in this study with particular attention paid to the growth of related industries like pharmaceuticals and hospitality as well as the GDP employment creation and foreign exchange earnings. Through the use of secondary data and comparative analysis with nations such as Thailand and Malaysia the study identifies India’s areas of strength and policy need. The results show considerable economic contributions but they also highlight issues like regulatory gaps development that is centred on cities and threats to access to domestic healthcare. There are strategic suggestions made to support inclusive growth improve quality control and match medical tourism with national healthcare and economic objectives. In order to improve the sectors sustainability and equity future research directions are also recommended.